Background and Meaning of the Scene on the Ferry in L. N. Tolstoy’s Novel Resurrection - Nadezhda G. Mikhnovets; Maria R. Koposova (Два века русской классики, 2022)
In the article, the scene on the ferry became the subject of a special study for the first time. Consideration of this scene in the historical and cultural aspect showed that the Old Believer theme, initiated by the letter of the runner A. V. Vlasov, set the final chapters of the novel Resurrection on an epic scale in understanding the fateful changes taking place in Russia at the end of the 19th century. The article reveals that the author of the novel wedged diametrically opposite ideas belonging to the folk thinker V. K. Sutaev. As a result, the author outlined a perspective for coordinating the old man’s differently directed judgments, it implies “non-resistance to evil by violence.” The final conclusion is made that the scene on the ferry grows out of the history of the statehood of pre-Petrine and Peter the Great times, which by the end of the 19th century was losing its essential foundations and degenerating into violence, as well as from the history of the original popular movement of the people in search of truth — as in the desired the prospect of finding a loving unity for all, and in the real danger of struggle and protest.